1992
DOI: 10.1002/art.1780350202
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Prospective Study of Methotrexate in the Treatment of Rheumatoid Arthritis

Abstract: Objective. To determine the long-term efficacy and safety of low-dose methotrexate (MTX) in rheumatoid arthritis (RA).Method&. Eighty-four-month open prospective trial at a single academic rheumatology center.Results. Twenty-six patients were enrolled in a prospective study of the long-term efficacy of MTX in RA; a significant improvement had been demonstrated after 36 months of therapy. Twelve patients remained in the study at the 84-month visit; the mean weekly dosage of MTX was 10.2 mg. A significant improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
85
2
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(90 citation statements)
references
References 20 publications
(14 reference statements)
2
85
2
1
Order By: Relevance
“…These studies and those by Weinblatt and colleagues (7,8) have demonstrated that MTX can be continued over periods of as long as 7.5 years while maintaining improvement in the clinical features and functional status compared with baseline. This is noteworthy because enrollees in these investigations, which were begun in 1982, had active RA and, by definition, had failed therapy with several other disease-mo-g antirheumatic drugs (DMARDs).…”
Section: Safety Efficacy and Mortality In A Long-term Cohort Of Patmentioning
confidence: 78%
See 2 more Smart Citations
“…These studies and those by Weinblatt and colleagues (7,8) have demonstrated that MTX can be continued over periods of as long as 7.5 years while maintaining improvement in the clinical features and functional status compared with baseline. This is noteworthy because enrollees in these investigations, which were begun in 1982, had active RA and, by definition, had failed therapy with several other disease-mo-g antirheumatic drugs (DMARDs).…”
Section: Safety Efficacy and Mortality In A Long-term Cohort Of Patmentioning
confidence: 78%
“…This is noteworthy because enrollees in these investigations, which were begun in 1982, had active RA and, by definition, had failed therapy with several other disease-mo-g antirheumatic drugs (DMARDs). Weinblatt has recently reported that clinical improvement was sustained in his cohort over a period of 11 years, but no mortality or functional status data were reported (9).…”
Section: Safety Efficacy and Mortality In A Long-term Cohort Of Patmentioning
confidence: 95%
See 1 more Smart Citation
“…hFRβ expression is increased in certain leukemias, most consistently seen in chronic myelogenous leukemia and acute myelogenous leukemia (43,45). hFRβ expression is also increased in activated synovial macrophages, cells involved in the pathogenesis of rheumatoid arthritis and other inflammatory conditions including psoriasis and Crohn's disease (37,39,46,47).…”
mentioning
confidence: 99%
“…Compared with other, more traditional disease-modifying antirheumatic drugs (DMARDs), methotrexate has a more rapid onset of action, superior long-term effectiveness, and fewer cumulative toxicities (3)(4)(5)(6). Studies show that 80% of patients discontinue other DMARDs after 2 years, while at least 50% continue to take methotrexate for Ͼ5 years (7)(8)(9).…”
mentioning
confidence: 99%